Theology of War in Deuteronomy 20:12-13: Case Studies and Their Applications in Contemporary Church Life: Teologi Perang dalam Ulangan 20:12-13: Studi Kasus dan Aplikasinya dalam Kehidupan Gereja Kontemporer - Zega, Bonitha Devinatalia; Hutapea, Jusuf (MODERATE: Journal of Religious, Education, and Social, 2025)
Deuteronomy 20 provides a significant biblical passage on the concept of war and its theological implications. This study aims to examine the meaning and message contained in Deuteronomy 20:12-13, exploring the historical, cultural, and theological context behind these verses. The research uses a descriptive qualitative approach, relying on a literature review and interviews with key informants to analyze the text. The findings suggest that these verses illustrate a complex divine approach to war, justice, and peace, offering valuable insights for modern Christian practice and understanding. The study also addresses common misinterpretations of these verses and proposes a clearer understanding of their relevance today.   Contribution: This study contributes to a deeper understanding of biblical interpretations related to war theology. It also provides insights into the implications of ancient teachings on modern Christian practices. Finally, it challenges misconceptions about the relationship between faith and violence in the context of historical biblical teachings.   Ulangan 20 memberikan suatu ayat Alkitab yang signifikan mengenai konsep perang dan implikasi teologisnya. Penelitian ini bertujuan untuk memeriksa makna dan pesan yang terkandung dalam Ulangan 20:12-13, serta mengeksplorasi konteks historis, budaya, dan teologis di balik ayat-ayat tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan mengandalkan tinjauan pustaka dan wawancara dengan narasumber utama untuk menganalisis teks tersebut. Hasil penelitian menunjukkan bahwa ayat-ayat ini menggambarkan pendekatan ilahi yang kompleks terhadap perang, keadilan, dan perdamaian, serta memberikan wawasan berharga untuk praktik dan pemahaman Kristen masa kini. Penelitian ini juga mengaddress kesalahpahaman yang sering terjadi tentang ayat-ayat ini dan mengusulkan pemahaman yang lebih jelas mengenai relevansinya saat ini.   Kontribusi: Studi ini memberikan kontribusi untuk pemahaman yang lebih dalam tentang interpretasi Alkitab terkait teologi perang. Penelitian ini juga memberikan wawasan tentang implikasi ajaran kuno terhadap praktik Kristen modern. Terakhir, penelitian ini menantang kesalahpahaman tentang hubungan antara iman dan kekerasan dalam konteks ajaran Alkitab historis.